Straight to Jesus : Sexual and Christian Conversions in the Ex-Gay Movement. - Erzen, Tanya (University of California Press, 2006)
Focuses on the everyday lives of men and women at New Hope Ministry, a residential ex-gay program. This study traces the stories of people who have renounced long-term relationships and moved from other countries out of a conviction that the conservative Christian beliefs of their upbringing and their own same-sex desires are irreconcilable.
Keywords: New Hope Ministries -- Case studies.; New Hope Ministries; Church work with gay people -- California -- San Rafael -- Case studies.; Ex-gay movement -- California -- San Rafael -- Case studies.; Pastorale des personnes homosexuelles -- Californie -- San Rafael -- Études de cas.; Mouvement ex-gay -- Californie -- San Rafael -- Études de cas.; RELIGION -- Christian Life -- Social Issues.; RELIGION -- Christianity -- General.; Church work with gays; Ex-gay movement; California -- San Rafael; born again christians.; christian conversions.; christian lives.; christian ministries.; christian right.; christianity.; conservative christianity.; evangelical christians.; ex gay ministries.; ex gay movement.; gay identity.; gay men.; heterosexuality.; homosexuality.; human rights.; jesus.; lesbians.; lgbtq.; men and women.; new hope ministry.; nonfiction.; political rights.; religious transformation.; romantic relationships.; same sex desire.; sexual conversions.; sexual desire.; sexuality.; social history.; transnationalism.; Case studies